Mechanisms of antioxidants in the treatment of vitiligo in vivo: a systematic review (Research, Society and Development, 2022)
Vitiligo is characterized by skin discoloration in different body regions, and its prevalence in the world population can reach 1%. Its cause is still undefined but possibly related to biochemical, environmental, immunological, and genetic events. In addition, individuals with vitiligo present electrolyte disturbances in the melanocytes, and it has been one of the targets of studies for treating this pathology. This systematic review aimed to gather and evaluate in vivo studies that described the mechanism of action of antioxidants in vitiligo. PubMed, Web of Science, Embase, Science Direct, LILACS, Open Grey and Google Scholar were used as research sources. The search included all articles up to October 16, 2021, with no start date restrictions. The search yielded 390 articles, and 7 of these were selected according to the inclusion criteria. The compounds studied in the articles selected for this review were curcumin, Cold Atmospheric Plasma, butin, galangin, 2',3,4,4'-tetrahydrochalcone and its derivatives, 6-benzylaminopurine, piperine, chrysin, kaempferol, scopoletin, vitamin D3, caffeic acid, and luteolin. The results showed that the main mechanisms of action of antioxidants in the treatment of vitiligo are the increase in tyrosinase activity by increasing the synthesis of TYR and TRP-1, the positive regulation of the number of epidermal cells, the redox balance, activation and regulation of MITF, and malondialdehyde and cholinesterase/acetylcholinesterase content. Thus, these pathways can be considered targets for evaluating different antioxidant compounds to act in treating vitiligo.